A Study on Port Cooperation in the Tianjin and Hebei Areas Using Factor Analysis - Sun, Ying; He, Weida (Journal of Comparative International Management, 2008)
When China switched its economic development focus from the Changjiang-Zhujiang Delta to the Bohai Sea, Tianjin and Hebei became two of the fastest developing areas in the country. As the hub of logistics, the port system plays an important role in increasing the region’s economic development. This paper reviews port logistics in Hebei and Tianjin, and explains the necessity of port cooperation in these areas. An index system for port logistics competition is proposed using factor analysis. The results can be used to guide the positioning and development of each port based on its individual strength, thereby improving the port logistics of the entire area.